FEATURES OF CHORIORETINAL BLOOD FLOW IN PATIENTS WITH OPEN-ANGLE GLAUCOMA - S. I. Zhukova; T. N. Yuryeva; I. V. Pomkina; A. S. Grishchuk (Сибирский научный медицинский журнал, 2019)
The purpose of the study was to evaluate the features of hemodynamics in patients with intraocular pressure (IOP) fluctuations, to reveal differential diagnostic criteria for adequate monitoring of glaucoma course according to optical coherence tomography (OCT) with the function of angiography. Material and methods. 25 patients (25 eyes) with hypertensive POAG were examined. The study included OCT of the retina and optic disk with the function of angiography. Patients of the clinical group underwent a non-penetrating fistulizing operation followed by laser goniopuncture. The examination was performed before the operation, in the early postoperative period, 1 and 3 months after the surgical intervention. The control group was 12 people (24 eyes) without ophthalmic pathology of the corresponding age and sex. Results and discussion. The obtained results testify to the role of regional hemodynamics in the formation of glaucoma neuroopticopathy. The revealed hemodynamic disturbances in the form of the decrease in the thickness of the choroid, decrease in the density of the radial peripapillary, superficial vascular plexus, and the corresponding glaucomatous changes in the optic disk, the layer of nerve fibers and the ganglionic retina complex, allow speaking about hypoperfusion caused by the decrease in the metabolic needs of atrophied tissue. Surgical interventions used in the treatment of patients with glaucoma lead to an improvement in blood flow parameters. Retinal and choroidal vessels respond differently to intraocular pressure fluctuations, which indicate different mechanism of adaptation of the eye’s vascular system in response to the change in the ophthalmotonus. In this connection, the question arises of the need to determine the individual intraocular pressure.